The Impact of Additional Employee Income on Work Discipline and Employee Performance in the Public Sector: A Quantitative Study in Singkut District, Sarolangun Regency - Syaihu, Ilham Akbar (Golden Ratio of Human Resource Management, 2026)
This study investigates the influence of Additional Employee Income (TPP) on work discipline and employee performance, both partially and simultaneously, at the Singkut District Office, Sarolangun Regency. The research is motivated by empirical findings indicating low levels of employee discipline and suboptimal public service performance, as reflected in frequent tardiness and delays in service delivery. This study employed a quantitative research design using a survey method, with data collected through questionnaires distributed to 68 civil servants (ASN) as the total population of the study. The data were analyzed using the Generalized Linear Model (GLM) to examine the effect of TPP on work discipline and employee performance. The analysis reveals that TPP has a significant positive effect on work discipline (69.3%) and employee performance (59.1%). Simultaneously, TPP contributes 33% to the improvement of work discipline and employee performance. These findings indicate that consistent, fair, and timely implementation of TPP policies can enhance employee motivation, strengthen work discipline, and improve public service performance in the public sector. These findings imply that policymakers should ensure the consistency and timeliness of TPP implementation and integrate financial incentives with supervision and performance evaluation mechanisms to strengthen discipline and public service performance in the public sector. This study provides important implications for policymakers in optimizing performance-based incentive systems within local government institutions. This study provides important implications for policymakers in optimizing performance-based incentive systems within local government institutions.